Князь Владимир Святой и культура Киевской Руси глазами Титмара Мерзебургского - Мусин, А.Е. (Княжа доба: історія і культура, 2016)
Пропонується нове прочитання деяких “руських епізодів” Хроніки Тітмара Мерзебурзького. Уточнено хронологію частини з них й обґрунтовано гіпотезу, що одним з джерел Хроніки могли бути усні розповіді Бруно Кверфуртського. Ця інформація стосувалася, переважно, історії гріха та навернення князя Володимира Святого, яка була частиною його первісного житія, зафіксованого в Тітмара латиною на сто років раніше від Повісті временних літ. Відновлено логіку біблійних цитат в Хроніці та ПВЛ. Передбачається, що знаний з літопису “гарем” князя Володимира міг відігравати свою роль у слов’янських язичницьких культах, пов’язаних із забезпеченням плодючості землі. Згаданий у Тітмара загадковий lumbarum venereum інтерпретовано як амулет і атрибут любовної магії. Дано огляд археологічно засвідчених форм подібних амулетів. Етимологія імені Володимир, пов’язана з поняттям “мир” як “мир”, визнається оправданою і прийнятою у середньовічному суспільстві. Кількість церков у Києві (400) пояснюється середньовічними уявленнями про ідеальну суспільну структуру. Зустріч у Мерзебурзі в травні 1013 г. розглянуто як поворотний момент у зародженні інтересу німецьких інтелектуалів до Східної Європи. The article revises the “Russian episodes” of the Chronicle of Thietmar of Merseburg. The author refines the chronology of several episodes and demonstrates that the information of Bruno of Querfurt could be one of the sources of the Chronicle. It might concern the history of Vladimir the Saint, his pagan lust and conversion to Christianity, and makes part of primitive hagiographical tradition on the Prince dedicated to him. This tradition had been fixed by Thietmar one hundred years before the Primary Russian Chronicle. The logic of Biblical citations in the narrative on Vladimir the Saint has been reconstructed. The huge harem of Vladimir mentioned in the Russian Chronicle could play special role in the pagan Slavonic cult of the fertility of earth. The enigmatic lumbarum venereum mentioned by Thietmar has been interpreted as an amulet of the erotic medieval magic, and the survey of archaeologically known forms of such amulets has been done. The author studies the etymology of the name ‘Vladimir’ as linked to the idea of “power of peace”. Such interpretation had been accepted in the medieval society. The number of churches in Kiev (400) is explained through the imagination of the medieval mentality on the ideal social structures. The Merseburg meeting in the May, 1013 A.D., is regarded as a turning point for the interest of the German intellectuals towards the Eastern Europe.